The Phylogenetic Position of Anaplasma bovis and Inferences on the Phylogeny of the Genus Anaplasma - YBAÑEZ, Adrian Patalinghug (The Japanese Society of Veterinary Science, 2013)
The present study aimed to determine the complete citrate synthase (gltA) and heat-shock protein (groEL) gene sequences of Anaplasma bovis and to infer phylogenetic relationships within the genus Anaplasma. Multiple alignments from single and concatenated sequences of the 16S rRNA, gltA and groEL genes of the genus Anaplasma were subjected to phylogenetic analyses. Percent identities of A. bovis nucleotide sequences were found highest with A. phagocytophilum in gltA (65.4%) and groEL (79.8%). Single gene phylogenetic tree results assumed similar phylogenetic positions within the genus Anaplasma, except for A. bovis. However, consensus and concatenated sequence phylogenetic trees showed similar results, revealing 2 subgroups within the genus.